Electrochemical, optical and morphological characterizations of Cu doped ZnO nanostructure thin films prepared by spin coating method - Yağci, Özlem (Afyon Kocatepe Üniversitesi)
From nanotechnology point of view where conductivity is crucial, although it is essential to determine the electrochemical properties Cu doped ZnO nanostructure thin films produced by spin coating, there are rare studies in the literature. Therefore, in this study, the aim was to examine thouroughly the electrochemical properties of nanostructure thin films which were grown on glass substrates by using a facile and cost-effective spin coating method. The effects of the dopant on the morphological, optical and electrochemical properties of ZnO nanostructure thin films doped with Cu at different concentrations (0-50%) were investigated by SEM, XRF, FTIR, UV-vis, mechanical profilometer, and cyclic voltametry. The absorption spectra of the samples revealed that the energy band gap value decreased by the incereasing of Cu doping concentration. SEM images depicted that more spherical and homogeneous nanostructures formed with the doping of Cu. Electrochemical results showed that increasing the Cu doping ratio in ZnO nanoparticles results in higher electron transfer indicating that the conductivity of ZnO nanostructured thin films increases with Cu doping. It can be concluded that it is possible to produce more homogeneous, wider spectrum absorption capable and more conductive nanostructure thin films by a simple and inexpensive method. It is envisaged that the thin films obtained are promising for a wide range of nanotechnology applications.

İletkenliğin hayati olduğu nanoteknoloji açısından bakıldığında, spin kaplama ile üretilen Cu katkılı ZnO nanoyapılı ince filmlerin elektrokimyasal özelliklerinin belirlenmesi çok gerekli olsa da literatürde sınırlı çalışmalar bulunmaktadır. Bu nedenle bu çalışmada, kolay ve uygun maliyetli spin kaplama yöntemi kullanılarak cam altlıklar üzerine büyütülen nanoyapılı ince filmlerin elektrokimyasal özelliklerinin derinlemesine incelenmesi amaçlanmıştır. Katkının, farklı konsantrasyonlarda (%0-50) Cu katkılı ZnO nanoyapılı ince filmlerin morfolojik, optik ve elektrokimyasal özellikleri üzerindeki etkileri SEM, XRF, FTIR, UV-vis, mekanik profilometre ve döngüsel voltametri ile araştırıldı. Örneklerin absorpsiyon spektrumları, Cu katkı konsantrasyonunun artmasıyla enerji bant aralığı değerinin azaldığını ortaya çıkardı. SEM görüntüleri, Cu katkısıyla daha küresel ve homojen nanoyapıların oluştuğunu gösterdi. Elektrokimyasal sonuçlar, ZnO nanoparçacıklarında Cu katkılama oranının arttırılmasının daha yüksek elektron transferi ile sonuçlandığını göstermiştir ki bu da ZnO nanoyapılı ince filmlerin Cu katkılaması ile iletkenliğinin arttığını göstermektedir. Basit ve ucuz bir yöntemle daha homojen, daha geniş spektrumlu absorpsiyon yeteneğine sahip ve daha iletken nanoyapılı ince filmler üretmenin mümkün olduğu sonucuna varılmıştır. Elde edilen ince filmlerin çok çeşitli nanoteknoloji uygulamaları için umut verici olduğu öngörülmektedir.
Spin kaplama yöntemi ile hazırlanan Cu katkılı ZnO nanoyapılı ince filmlerin elektrokimyasal, optik ve morfolojik karakterizasyonları
Keywords: Copper; Zinc Oxide; Cyclic Voltametry; Electrochemical; Thin Film; Spin Coating; Bakır; Çinko Oksit; Döngüsel Voltametri; Elektrokimyasal; İnce Film; Spin Kaplama